2012
DOI: 10.1590/s2179-64912012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spine dysfunction signs and symptoms in individuals with temporomandibular disorder

Abstract: PURPOSE: To study the frequency of cervical spine dysfunction (CCD) signs and symptoms in subjects with and without temporomandibular disorder (TMD) and to assess the craniocervical posture influence on TMD and CCD coexistence. METHODS: Participants were 71 women (19 to 35 years), assessed about TMD presence; 34 constituted the TMD group (G1) and 37 comprised the group without TMD (G2). The CCD was evaluated through the Craniocervical Dysfunction Index and the Cervical Mobility Index. Subjects were also questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 24 publications
1
36
0
9
Order By: Relevance
“…These factors were not controlled and seem to be the main limitation of this study. Other studies have found a higher prevalence of cervical pain in patients with TMD with moderate or severe intensity (19) . In contrast, in the absence of association between TMD and the presence of cervical pain, it was observed that the majority (70.6%) of individuals who had cervical pain also presented TMD.…”
Section: Discussionmentioning
confidence: 80%
“…These factors were not controlled and seem to be the main limitation of this study. Other studies have found a higher prevalence of cervical pain in patients with TMD with moderate or severe intensity (19) . In contrast, in the absence of association between TMD and the presence of cervical pain, it was observed that the majority (70.6%) of individuals who had cervical pain also presented TMD.…”
Section: Discussionmentioning
confidence: 80%
“…However, after treating the TMJ disorder, a reduction in modulation following somatic maneuvers in the NECK region was found. This could be explained by the possible effect of the TMJ disorder on the NECK ascending pathways, resulting in a modulation in this region as well [91][92][93][94] . This suggests to carefully evaluate the somatic component, especially when a notable history of TMJ dysfunction is suspected and no other significant risk factors are present.…”
Section: Comments On This Casementioning
confidence: 99%
“…The development of utility electronics, sedentary mode of life and locomotion, coupled with a lack of health awareness are the key factors contributing to vertebral dysfunctions [3]. Nowadays, CSD is regarded as a common disease and includes a group of symptoms with pain, limited mobility, and tenderness [4]. Furthermore, the early symptoms are often ignored or masked by the use of easily available over-the-counter (OTC) analgesics [5].…”
Section: Introductionmentioning
confidence: 99%